Preliminary In Vitro Antiplatelet Potential of Ipomoea pes-caprae from North Lombok with Adenosine Diphosphate-Induced Platelet Aggregation - Ilsa Hunaifi; Dewi Suryani; Lalu Husnul Hidayat; Muhammad Naufal Farras Ananta; Muhammad Iqbal Farobbi; Nisa Isneni Hanifa; Raisya Hasina (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Cardiovascular diseases, particularly ischemic stroke, remain a global health burden, necessitating potential candidate for further antiplatelet with fewer side effects. Objectives: This study aimed to evaluate the antiplatelet potential of ethanolic extracts from the leaves and stems of Ipomoea pes-caprae (Katang-katang) from North Lombok, Indonesia, through ADP-induced platelet aggregation. Phytochemical screening, total tannin quantification, and in vitro antiplatelet assays were conducted. Methods: The leaves and stems were macerated with 96% ethanol, followed by qualitative phytochemical tests, Folin-Ciocalteu-based tannin analysis, and platelet aggregation inhibition assays using human platelet-rich plasma. Results: The extracts contained alkaloids, flavonoids, and tannins, with higher tannin levels in leaves (4.02 ± 0.02 mgEAT/g) than stems (3.67 ± 0.17 mgEAT/g). Concentration-dependent antiplatelet activity was observed, with leaf extracts showing inhibition (85.9% at 2000 μg/mL) compared to stems (79.5%) and aspirin (77.3%). IC₅₀ values were 727.78 μg/mL (leaves) and 349.95 μg/mL (stems). Statistical analysis confirmed significant differences across concentrations (p < 0.05). Conclusion: These findings demonstrate that Ipomoea pes-caprae exhibits potent antiplatelet activity, attributed to its tannin and phytochemical content, with leaves being more effective. Although these findings suggest preliminary antiplatelet potential, further analysis is required to validate the method using aspirin IC₅₀, and subsequent in vivo and pharmacological investigations are necessary before therapeutic application can be claimed.